Desain Dan Manufaktur Hopper Penyalur Pupuk Menggunakan Valve Metering Mechanism Pada Cultivator Untuk Pemupukan Kelapa Sawit - Darmansyah Darmansyah; Dodi Sofyan Arief; Muftil Badri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fertilization plays an important role in increasing the production of palm oil. Fertilization by manually deployed using the hand is considered less effective because the dose of fertilizer is not uniform and improper fertilization methods. The purpose of thisresearch is to design and make the hopper (tank fertilizer distributor) for precise fit required dose and volume of uniform fertilizer for each tree. The case study method is used to getinformation about fertilization technique and dose of fertilizer. The information obtained is used to design and acquire the dimensions, the shape of the hopper is made. Design methodusing descriptive design french. Once the image is finished then print out the pictures do the work that will be done the manufacturing process. From the calculation and testing obtained capacity ofthe reservoir tank is 7.5 liters, volumemetering 1 0:09 L, metering 2 0.17 L, metering 30.26 L with dimensions of 200 mm × 150 mm × 283 mm. From the simulation results obtained structural analysis of the maximum value of the safety factor 15 minimum safety factor of 3.49, while the maximum displacement and displacement 0.04568 minimum 0 results shows that the hopper is safe to use. Hopper performance results have been obtained through the testing process with an average dose of the valve 1 0.07 kg (urea), 0.08 kg (TSP), valve 2 0.12 kg (urea), 0.14 kg (TSP fertilizer), and valve 3 0.17 kg (urea), 0.19 kg (TSP).Keywords: Design, fertilizationtechnology, fertilizationmechanisms, valve metering mechanism.